Focusing on the underserved : immigrant, refugee, and indigenous Asian American and Pacific Islanders in higher education - Museus, Samuel D.; Agbayani, Amefil, 1943-; Ching, Doris (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
Recent discussions and dissemination of information regarding the rapid growth of Asian Americans and Pacific Islanders (AAPI) across our nation are creating some awareness among administrators and educators in higher education institutions regarding the extensive diversity of AAPIs, the struggles of some AAPI populations in pursuing and succeeding in higher education, and the lack of support for their educational success. National discourse on AAPIs among educators, policymakers and AAPI communities underscores the need for more research--including more relevant research--that can inform policy and practice that will enhance educational opportunities for AAPIs who are underserved in higher education.The book focuses on diverse topics, many of which do not appear in the current literature. The chapters are authored by an array of distinguished and emerging scholars and professionals at various universities and colleges across the nation. The authors, whose insights are invaluable in understanding the diverse issues and characteristics that affect the educational success of underserved AAPI students, and they represent the ethnicities and cultures of Cambodian, Chinese, Guamanian/Chamorro, Filipino, Hispanic, Hmong, Japanese, Korean, Laotian, Native Hawaiian, Okinawan, Samoan, Vietnamese, and multiracial Americans. The authors not only integrate theoretical concepts, statistical analyses, and historical events, but they also merge theory and practice to advocate for social justice for AAPIs and other underrepresented and underserved ethnic minority groups in higher education.